Ground Simulation Test of 2D Dynamic Overload Environment of Fuze Launching - Zhibo Wu; Tiehua Ma; Yanbing Zhang; Hongyan Zhang (Shock and Vibration)
The fuze launch process is subjected to backseat and spin overloads. To address this issue, a loading method of a 2D dynamic acceleration environment was developed in this study for testing fuze antioverload performance on ground. The techniques of flywheel energy storage, high-speed impact, and centrifugal rotation in the track are combined in a dynamic analysis and simulation. First, the flywheel is rotated at a constant speed by a variable-frequency motor to obtain high kinetic energy. Second, an impact hammer is instantaneously released on the specimen at a high speed, loading the backseat acceleration environment. Finally, the impact hammer is retracted, and the specimen is rotated in the track instead of spinning around its axis, thereby loading the centrifugal acceleration environment. The peak value and pulse width of the 2D overload acceleration can be adjusted by changing the speed of the flywheel and buffers in the abovementioned process. The experimental and simulation results observed that the peak value of backseat acceleration could reach 34,559 g, the pulse width was approximately 400 μs, and the peak value of the centrifugal acceleration was 1,020 g. The study results showed that the proposed approach fulfills the requirements of the 2D overload simulation test of the micro-electromechanical system (MEMS) fuze safety and arming mechanism. The proposed loading method has been successfully applied to ground simulation tests of the MEMS fuze safety and arming mechanism.